Acute and Protracted Prenatal Stress Produce Mood Disorder-Like and Ethanol Drinking Behaviors in Male and Female Adult Offspring - Dong, Erbo; Zhang, Huaibo; Chu, Alison; Pandey, Subhash C. (Frontiers in Behavioral Neuroscience, 2022)
Background: Alcohol use disorder (AUD) is a complex and chronic relapsing brain disease, which is often co-morbid with psychiatric disorders including anxiety and depression. AUD phenotypes differ in men and women. Although genetic factors play an important role in its pathophysiology, epidemiologic evidence suggests that during prenatal development, individuals are more vulnerable to the negative effects of environmental factors that may predispose them to AUD later in life. We explored the effects of prenatal stress on the development of AUD phenotypes as well as anxiety and depression like behaviors using rat model. Methods: Timed pregnant Sprague Dawley dams were used. Dams in the control group were left undisturbed throughout gestation, whereas dams in stress groups were either subjected to protracted or acute restraint stress under bright light. At adulthood, the anxiety-like, ethanol drinking, and sucrose drinking behaviors were measured using the Light/Dark Box test and two-bottle free-choice procedure. Results: Compared to the control group, both the male and female offspring in the stress groups exhibited anxiety-like behavior and consumed significantly higher amounts of ethanol in which the acute stress group demonstrated the higher ethanol preference. Moreover, male but not female offspring from the stress groups had decreased sucrose preferences. Conclusion: These findings suggest that protracted and acute prenatal stress in late pregnancy can induce in anxiety-, depressive-like behaviors and excessive ethanol intake in adult offspring.